Congenital herpes simplex with ophthalmic and multisystem features: a case report - Samuel Montenegro Pereira; Rian Vilar Lima; Maria Carolina Rocha Muniz; Marcus Breno Farias Araújo; Luiz de Moraes Ferreira Júnior; Juliana Tiburtino de Queiroz Sales Martins; Cláudia Faustino Coelho Luz; David Antônio Camelo Cid; Daniel da Rocha Lucena (BMC Pediatrics, 2023)
Abstract Background Neonatal herpes simplex virus (HSV) infection is rare and has significant morbimortality rates. Approximately 85% of newborns are infected intrapartum, and risk factors for mother-to-child transmission include vaginal delivery, primary maternal infection, and prolonged rupture of membranes. Neonatal HSV can manifest with isolated mucocutaneous lesions, neurological involvement, or disseminated disease. In general, herpetic infection can cause blepharoconjunctivitis or keratitis. We report a rare case of congenital herpes with ophthalmologic manifestations and multisystemic involvement. Case presentation A preterm infant, born at 32 weeks and 2 days, with presumed neonatal infection developed intestinal and respiratory complications, as well as hyperemic lesions on the left nostril and oral mucosa. An ophthalmological assessment was requested and brought up the suspicion of HSV infection, indicating empirical treatment with endovenous acyclovir. Later, a new ocular examination was suggestive of panuveitis. Afterward, serum IgM antibodies to HSV-1 and HSV-2 were positive. Proper antiviral therapy led to an improvement in the condition. Discussion Neonatal herpes is associated with a high risk of persistent skin lesions, long-term neurological disability and other lasting sequelae. It is essential to consider HSV infection in cases of neonatal conjunctivitis, especially in patients with an epithelial defect and no improvement after initial treatment with topical or systemic antibiotics. Conclusions In the management of neonatal HSV, early diagnosis is essential for the timely initiation of antiviral therapy. Our report highlights that ocular assessment can be crucial in the correct diagnostic investigation of this condition.